Land and soil management: Promoting healthy soils for healthier agricultural systems - Koo, Jawoo; Nkonya, Ephraim M.; Azzarri, Carlo; Cox, Cindy M.; Johnson, Timothy; Komarek, Adam M.; Kwon, Ho Young; De Pinto, Alessandro; Roberts, Cleophelia; Zhang, Wei (International Food Policy Research Institute, 2016)
Soil and land management are essential for a sustainable food supply and ecosystems. Healthy soils can support sustainable agricultural production, mitigation of the impacts of climate change, and other ecosystem services. Interventions that show promise for improving soil health include investment in sustainable intensification technologies, climate-smart agriculture, and ecosystem-level management.